Influence Mf Nitrogen and Phosphorus on Yield and Seed Quality of French Bean (Bangladesh Agronomy Journal, 2016)
The experiment was conducted at the research field of Agronomy Division, Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur during Rabi (winter) season of 2010-11 to 2011-12 to determine the optimum rate of nitrogen and phosphorus fertilizer on yield and seed quality of French bean. A randomized complete block design was followed with ten treatment combinations such as N0P0, N0 P44, N50 P44, N100 P44, N150 P44, N200 P44, N150P0, N150P22, N150P33 and N150P55. Number of pods and yield of French bean were significantly increased with the increase in N (150) and P (44) kg ha--1. Averaged over the years, maximum number of pod (9.45 plant-1) and seed yield (1563.33 kg ha-1) were obtained when N and P were applied at the rate of 150 and 44 kg ha-1, respectively while lowest yield to N0P0 treatment in both the years. The treatment (N150P44 kg ha-1) gave the highest seed yield which was 51.4 and 54.30% higher than the control. Quality in terms of germination percentage and vigour index of harvested seed was also significantly influenced by higher doses of N and P while the lowest seed quality from plants that received no fertilizer in both the years.Bangladesh Agron. J. 2015, 18(2): 1-8